PENGARUH PELEBARAN JALAN BY PASS TERHADAP SOSIAL EKONOMI MASYARAKAT DI KECAMATAN LUBUK BEGALUNG KOTA PADANG - Fikri Hidayatullah; yurni suasti; Fitriana Syahar (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
Abstract . This study aims to determine the state of residence, environmental conditions, type of work Community income level before and after widening the By Pass road. The type of research used is a qualitative descriptive study with the subject of research is the community around the By Pass Lubuk Begalung District, Padang City. The results of the study found that there were changes in housing and community environment in the form of distance, environmental comfort, and conversely did not experience changes in the type of building, building area, environmental cleanliness and the number of workers. There is a change in the type of work and the level of income of the community in the form of changes, income, profits, and vice versa, there are no changes, permanent employment, side jobs and business development.